1999
DOI: 10.1103/physrevb.60.5456
|View full text |Cite
|
Sign up to set email alerts
|

Raman scattering by LO phonon-plasmon coupled modes inn-type InP

Abstract: We have studied LO phonon-plasmon coupled modes by means of Raman scattering in n-InP for carrier densities between 6ϫ10 16 and 1ϫ10 19 cm Ϫ3 . A line-shape theory based on the Lindhard-Mermin dielectric function that takes into account the nonparabolicity of the InP conduction band as well as temperature and finite wave-vector effects is used to fit the Raman spectra and extract accurate values of the electron density. The results obtained from the Lindhard-Mermin model are compared with the charge density de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 34 publications
(55 reference statements)
3
66
0
3
Order By: Relevance
“…Numerous studies have been reported on inelastic light scattering by LOPCMs in III-V semiconductors, and different models have been developed to analyze the LOPCM behavior. [39][40][41] The analysis of the LOPCM peaks is widely employed to evaluate in a contactless and nondestructive manner the free-carrier density of the samples. However, only a few reports have been devoted to investigate the pressure dependence of the LOPCMs.…”
Section: Long-wavelength L − Coupled Modesmentioning
confidence: 99%
“…Numerous studies have been reported on inelastic light scattering by LOPCMs in III-V semiconductors, and different models have been developed to analyze the LOPCM behavior. [39][40][41] The analysis of the LOPCM peaks is widely employed to evaluate in a contactless and nondestructive manner the free-carrier density of the samples. However, only a few reports have been devoted to investigate the pressure dependence of the LOPCMs.…”
Section: Long-wavelength L − Coupled Modesmentioning
confidence: 99%
“…At high carrier concentrations in n-InP, a Drude model underestimates carrier concentration because band nonparabolicity is ignored. 7,50 Although the material systems are different, these effects probably still contribute to the differences between Hall effect and Raman spectroscopic measurement of hole concentration. In addition, at high hole concentrations, the neglect of inter-valence band scattering may Table I.…”
Section: Comparison Of Raman Spectroscopic and Hall Effect Measurementioning
confidence: 99%
“…The Drude model ignores Landau damping, spatial dispersion of the plasmon, band nonparabolicity, and finite temperature effects. 7,50,54 Despite the limitations of the Drude model, this model has the advantage that it requires the fewest input parameters and is computationally inexpensive, particularly compared to the Lindhard-Mermin model.…”
Section: P-type Gasb Raman Spectramentioning
confidence: 99%
See 2 more Smart Citations